Global google trends for construction demonstrate low search volume index for stress, mental and suicide - Craig Steven McLachlan; Hang Truong (BMC Research Notes, 2023)
Abstract The comparison of Google internet searches for English words in construction for “construction stress”, “construction mental” and “construction suicide” with reference to “construction worker” has not previously been undertaken. It is important to understand internet interest across these 3 terms as all are relevant to mental health and stress in construction. Suicide risk is significantly complex and multifactorial. Our aim is to investigate internet search interest across construction with a focus on mental, stress and suicide, and determine whether there is consistent interest across these search terms. Methods: Using Google Trends, data on global search queries we compared “construction mental” or “construction stress” and “construction suicide”. Two time periods were compared, the last 5 years and the last 24 months, both till December 8th, 2022. The relationship between web search interest, reflected by search volume index (SVI) for society and community versus the business and industrial category and health category were evaluated. Results: Open category searches on Google trends for the key words “construction mental” or “construction stress” demonstrated moderate SVI peaks over a 5-year period. Sub-group analyses for the industrial and business category demonstrated consistent low interest in suicide compared to search terms related to stress or mental health. Conclusion: There is limited online interest in construction mental and stress and even less interest in suicide.